STUDI LITERATUR PERAN BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) TERHADAP PENINGKATAN KINERJA UMKM DI INDONESIA - Lubis, Nurliza (ISTIQRA: Jurnal Hasil Penelitian, 2024)
This study analyzes the role of Sharia People's Financing Banks (BPRS) in improving the performance of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Using a literature review method, this research examines various academic publications and credible reports discussing the contributions of BPRS to MSME development. The findings indicate that BPRS plays a significant role by providing sharia-based financing such as murabahah and musharakah, which help MSMEs overcome capital constraints. Furthermore, BPRS serves as a social intermediary by providing training and consultations to enhance MSME capacities. The advantage of the profit-sharing system implemented by BPRS offers flexibility for MSMEs without the burden of fixed interest, encouraging productivity and business sustainability. However, the study also identifies several challenges, such as limited working capital, the need for product innovation, and low financial literacy among MSMEs. These findings highlight that BPRS impacts not only at the microeconomic level but also contributes to local economic development through increased job absorption, regional GDP growth, and reduced economic inequality. This study is expected to provide academic contributions and serve as a foundation for formulating policies to strengthen the role of BPRS in empowering MSMEs in Indonesia